2017
DOI: 10.1111/ijfs.13676
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biochemical properties and thermal inactivation of membrane‐bound polyphenol oxidase from three apple cultivars (Malus domestica Borkh)

Abstract: A comparative study of the properties of membrane-bound polyphenol oxidase (mPPO) from three apple cultivars, namely Red Fuji (FJ), Granny Smith (GS) and Golden Delicious (GD), was carried out for the first time. Data indicate that mPPOs from three cultivars exhibit significantly different properties. GS mPPO had the strongest affinity to catechol, but FJ mPPO had the highest maximum velocity. Red Fuji (FJ) mPPO had the significantly higher activity than those of GD and GS mPPOs. Red Fuji (FJ) mPPO had the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…unicolor cotton PPO. These results are consistent with many previous studies, where Z-value for different PPOs usually ranges between 10 and 18°C (Benaceur et al, 2019;Liu et al, 2018; . The ΔS represents the reversibility of the transformation, the disorder, and/ or homogeneity degree of the system (Gouzi et al, 2012).…”
Section: Thermal Inactivationsupporting
confidence: 94%
See 1 more Smart Citation
“…unicolor cotton PPO. These results are consistent with many previous studies, where Z-value for different PPOs usually ranges between 10 and 18°C (Benaceur et al, 2019;Liu et al, 2018; . The ΔS represents the reversibility of the transformation, the disorder, and/ or homogeneity degree of the system (Gouzi et al, 2012).…”
Section: Thermal Inactivationsupporting
confidence: 94%
“…Christoffersen (2016) also found two optimal pH values of 5.0 and 7.0 when studying avocado PPO. Coincidentally, two optimum pH levels were also founded in apple (Liu et al, 2018) and edible desert truffle (Gouzi, Depagne, Benmansour, & Coradin, 2013). This difference might be due to the two isoenzymes with different properties or the two ionization states of the substance generated from the enzyme and substrate reaction (Weemaes, Ludikhuyze, Van den Broeck, Hendrickx, & Tobback, 1998).…”
Section: Ph Optimum and Stabilitymentioning
confidence: 99%
“…Similarly, PPO activity from blueberry was at 420 nm (Siddiq & Dolan, 2017;Terefe, Delon, Buckow, & Versteeg, 2015). The highest wavelength of absorbance at 410 nm was automatically assayed for PPO from Fuji apple (Fang, Zhao, Gan, & Ni, 2015) and at 412 nm was determined for Whangkeumbae pear (Zhou et al, 2018).…”
Section: Parameters For Measurement Of Ppomentioning
confidence: 99%
“…Therefore, enzymatic browning is believed to be one of the great challenges for vegetable and fruit industries (Anaya-Esparza et al, 2017;Sikora & Świeca, 2018). Several techniques including removing oxygen, heating, and high pressure have been regarded as useful measures to prevent enzymatic browning (Fang, Han, & Ni, 2017;Gavirangappa, Harshini, Arugakeerthy, Kulathooran, & Sr, 2018;Tinello & Lante, 2018). Moreover, the addition of inhibitors, which are non-toxic and highly active at low concentrations, is also an effective way to inhibit the browning reaction (Moon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This result shows that mPPO was more easily inactivated, compared with the released PPO. Previous studies demonstrated that the Fuji apple mPPO lost only 16.7% at 65 °C for 10 min (Liu et al ., ). The different results might due to the sufficient heating by RF treatment and higher treatment temperature.…”
Section: Resultsmentioning
confidence: 99%